Tindak Pidana Penjebolan Aplikasi Sistem Transportasi Online Ditinjau Dari Undang-Undang Informasi Dan Transaksi Elektronik : Studi Putusan Pengadilan Negeri Medan Nomor 1507/Pid.Sus/2018/Pn.Mdn - Fadilah Khoirinnisa Harahap; Madiasa Ablisar; Muhammad Hamdan; Mahmud Mulyadi (Universitas Sumatera Utara, 2019)
Abstract. Online-based transportation business has spread to various cities in Indonesia, one of them is in the city of Medan. Various cheating modes are carried out by several driver partners, including fictitious orders, using the Fake GPS application to cheat the system, and using additional applications to not take orders without reducing the performance of receiving orders from partners. Based on the above problems, the problems with this thesis are as follows: What is the regulation regarding the crime of breaking into online transportation system applications in the Information and Electronic Transactions Law? How does the evidentiary system relate to the crime of breaking into online transportation system applications? What is the analysis of the judges' consideration of the Medan District Court's decision regarding the criminal offense of the application of the online transportation system? The research method used is normative legal research. The nature of this research is descriptive-analytic with the Legislative Approach (legal approach), case approach. In normative legal research, the data used are secondary data. Secondary data obtained by conducting research on primary legal materials, secondary legal materials, and tertiary legal materials. The criminal act of breaking into an online transportation system application is regulated in Article 30 paragraph (3) of Law Number 19 the Year 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). The Negative Proof System is a proof system used under Article 183 of the Criminal Procedure Code which is an attempt to find material truth. The judges decide and convict based on the facts of the trial, the defendant in committing his actions using electronic media as his object, this is in accordance with the elements contained in Article 30 paragraph (3) of the ITE Law, which specifically regulates acts that violate, breakthrough, surpassing, or breaking down the security system, in this case the online transportation system application. Keywords: criminal acts, inroad to system applications, online transportation